The influence of the application of government accounting standards and local government internal control on the quality of financial reporting information - Yosi Juita (Indonesia Accounting Research Journal, 2023)
This study aims to determine the effect of applying government accounting standards on the quality of financial reporting information and the influence of regional government internal control on the quality of financial reporting information of the Regional Work Unit (SKPD) of Bukittinggi City. This research is a causative descriptive type which describes the facts that occur clearly and looks at the effect of each causal variable (X) on the effect variable (Y). The population of this study consisted of 87 civil servants (PNS) government agencies and accounting staff of the Regional Work Unit (SKPD) of Bukittinggi City, so the sample for this study was total sampling because the population was less than 100 objects.∝5% (0.05), 2) there is a significant influence between Local Government Internal Control on the quality of financial report information with a t value of 3.184 or a significant level of 0.004, the value is smaller than the significant level∝5% (0.05). It is hoped that this research can make a positive contribution to the Regional Apparatus Unit (SKPD) of the City of Bukittinggi.